FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN GOUT ARTHRITIS MASYARAKAT MELAYU - Eni Angriani; Ari Pristiana Dewi; Riri Novayelinda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
This research aimed to find out the factors associated with the incidence of gout arthritis in Malay society based on community health centre Rumbai Pesisir Pekanbaru. Cross sectional design. The sample of this research consist of 93 respondents by using cluster sampling technique. The instrument of this research are questionnaire, food recall questionnaire and digital uric acid level. The result obtained that the majority of sample are female respondents (62,4%), age 51-60 years (50,5%), junior high school graduated (40,9%), story of diaseases (76,3%), obesity experience (45,2%), high purine intake (59,1%), insidence gout arthritis in Malay society (74,2%). The chi square analysis showed that there has been a significant relationship between the disease story of the respondent, obesity, and purin intake to incidence gout arthritis in Malay society as story of diseases (p value = 0,000), obesity (p value = 0,000), purine intake (p value = 0,000). Based on the results of this research, expect to community health centre provides a prevention program to prevent gout arthritis by giving counseling about the factors associated with incidence gout arthritis in Malay society, especially to Malay society. Keywords: Gout arthritis, Malay society